14-3-3ζ Overexpression Defines High Risk for Breast Cancer Recurrence and Promotes Cancer Cell Survival - Neal, Christopher L. (2009)
The ubiquitously expressed 14-3-3 proteins are involved in numerous important cellular functions. The loss of 14-3-3σ is a common event in breast cancer; however, the role of other 14-3-3s in breast cancer is unclear. Recently, we found that 14-3-3ζ overexpression occurs in early stage breast diseases and contributes to transformation of human mammary epithelial cells. Here, we show that 14-3-3ζ overexpression also persisted in invasive ductal carcinoma and contributed to the further progression of breast cancer. To examine the clinical impact of 14-3-3ζ overexpression in advanced stage breast cancer, we performed immunohistochemical analysis of 14-3-3ζ expression in primary breast carcinomas. 14-3-3ζ overexpression occurred in 42% of breast tumors and was determined to be an independent prognostic factor for reduced disease-free survival. 14-3-3ζ overexpression combined with ErbB2 overexpression and positive lymph node status identified a subgroup of patients at high risk for developing distant metastasis. To investigate whether 14-3-3ζ overexpression causally promotes breast cancer progression, we overexpressed 14-3-3ζ by stable transfection or reduced 14-3-3ζ expression by siRNA in cancer cell lines. Increased 14-3-3ζ expression enhanced anchorage independent growth and inhibited stress-induced apoptosis, whereas downregulation of 14-3-3ζ reduced anchorage independent growth and sensitized cells to stress-induced apoptosis via the mitochondrial apoptotic pathway. Transient blockade of 14-3-3ζ expression by siRNA in cancer cells effectively reduced the onset and growth of tumor xenografts in vivo. Therefore, 14-3-3ζ overexpression is a novel molecular marker for disease recurrence in breast cancer patients and may serve as an effective therapeutic target in patients whose tumors overexpress 14-3-3ζ.